2014
DOI: 10.4025/actascibiolsci.v36i3.19791
|View full text |Cite
|
Sign up to set email alerts
|

<b>Effect of administering a diet contamined with fumonisins on the kidneys of wistar rats

Abstract: Fumonisins (FBs) are mycotoxins produced by Fusarium molds. Several works have shown contamination of maize by this toxin. Fumonisin B1 (FB-1) is found in greatest proportion (about 70%), resistant to several industrialization processes. In that context, the objective of this work was to analyze the effect of administering a diet contaminated with FB-1 on the morphophysiology of the kidneys of 21-day old male Wistar rats. The animals were divided into 2 groups: G0 (with animals receiving feed free of FBs) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…The results of this study showed that exposure to FB1 caused many histological changes in the kidneys of first-generation offspring, such as glomerular atrophy, expansion of the Bowman's space, and inflammation. This is in agreement with a previous study showing the occurrence of similar histopathological changes in the renal tubules and the development of fibrosis [13,14]. Moreover, early alterations brought on by FB1 include increased excretion of high-and low-molecular-weight proteins, reduced osmolality, and increased urine volume [15].…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study showed that exposure to FB1 caused many histological changes in the kidneys of first-generation offspring, such as glomerular atrophy, expansion of the Bowman's space, and inflammation. This is in agreement with a previous study showing the occurrence of similar histopathological changes in the renal tubules and the development of fibrosis [13,14]. Moreover, early alterations brought on by FB1 include increased excretion of high-and low-molecular-weight proteins, reduced osmolality, and increased urine volume [15].…”
Section: Discussionsupporting
confidence: 93%
“…Though the dose applied [ 32 ] was lower as in our treatment, authors also provided evidence of single cell necrosis at 10 ppm, which was not found in our present work. Higher dose (700 vs. 600 μg/kg BW) of FB 1 (provided as fungal culture in the diet) and longer exposure (42 vs. 10 days) to ours did not affect the creatinine level in plasma, water intake, osmolarity and urinary excretion of sodium, while increased urine volume and potassium excretion and caused mild tubulointerstitial changes in the outer cortex of the kidney [ 51 ]. With regard to the histopathological alterations to the kidney in a long exposure, Gelderblom et al [ 49 ] further described atrophic, pale, and the irregular outline and presence of numerous cortical and medullary retention cysts of the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…In order to investigate the effect of FB 1 on kidney, Venancio et al (2014) fed groups of 8 Wistar rats with diets containing either no FBs or 6 mg FB 1 /kg (obtained by addition of Fusarium verticillioides culture material) equivalent to 0.7 mg FB 1 /kg bw, for 42 days. FB 1 did not affect feed intake, body weight and growth, creatinine levels in plasma, water intake, osmolarity and urinary excretion of sodium while increased urine volume and potassium excretion was observed which was paralleled by mild tubulointerstitial changes in the outer kidney cortex.…”
Section: Ratsmentioning
confidence: 99%